High risk industries for advanced lightning protection system - Kalagotla Chenchireddy; P. Nagabushanam; Radhika Dora; Vadthya Jagan; Shabbier Ahmed Sydu; Nunavath Praveen (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Lightning strikes are a serious risk for high-risk facilities like oil and gas plants, mines, explosive storage, and data centers. These places hold the sensitive equipment and dangerous materials, and a lightning strike can cause major damage, leading to expensive downtime or even disastrous events such as fires or explosions. That’s why having a strong lightning protection system is not just a matter of following rules, but it is crucial for protecting both people and property. The complete lightning protection solutions designed to meet the specific needs of these critical industries. The services include lightning simulations and both isolated and attached lightning protection systems. This study investigates the real-time installation and testing of advanced lightning protection systems across high-risk industries like oil and gas plants, mines, explosive storage, and data centers. This ensures that the facility stays safe and continues to operate, even during severe weather. By investing in an effective lightning protection system, you can help secure your assets and keep everyone safe, focusing on what really matters in your industry.